PENGARUH TAX PLANNING DAN TAX AVOIDANCE TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN KEUANGAN SEKTOR ASURANSI - Manafe, Joya; Widyastuti, Tri (Investama : Jurnal Ekonomi dan Bisnis, 2025)
Taxes are the country's largest income, but tax entities are seen as obstacles. Tax planning and tax avoidance strategies are part of managerial decisionmaking that can affect investor perception and affect the market value of a company. This research aims to test the effect of tax planning and tax avoidance on the corporate value of the insurance sector listed on the Indonesia Stock Exchange (IDX) during the period 2021- 2024. This study uses a quantitative approach with associative research types. The data used is secondary data in the form of annual financial statements from nine insurance companies, obtained through the official website of the IDX and the website of each company. Tax planning (ETR), tax avoidance (BTD), and corporate value variables using Tobin's Q. Analysis of the data was conducted using a classical assumption test, multiple linear regression and hypothesis test with the help of SPSS software version 27. Research results showed that partial tax planning did not have a significant effect on corporate value, while tax avoidance had a significant effect. Simultaneously, the two variables did not have a significant effect on corporate value. This indicates that the tax efficiency strategy in the insurance sector is not strong enough to directly affect corporate value.